Tehnik Akupresure untuk Mengatasi Disminore pada Remaja - Furhatin, A'yun; Ari Andayani; Ika Ratichya Ningsihi (Universitas Ngudi Waluyo, 2024)
Dysmenorrhea is a condition that occurs during menstruation which can cause disruption to activities and requires treatment if the symptoms are severe, and are expressed through pain or tenderness in the pelvic and abdominal areas. Most women in Indonesia who experience dysmenorrhea do not report it or visit a doctor. As many as 90% of Indonesian women have experienced dysmenorrhea. secondary dysmenorrhea. Perform acupressure techniques which consist of 4 techniques. First, do the massage technique for the LI 4